2021
DOI: 10.1007/s00500-020-05479-2
|View full text |Cite
|
Sign up to set email alerts
|

Short text similarity measurement methods: a review

Abstract: Short text similarity measurement methods play an important role in many applications within natural language processing. This paper reviews the research literature on short text similarity (STS) measurement method with the aim to (i) classify and give a broad overview of existing techniques; (ii) find out its strengths and weaknesses in terms of the domain the independence, language independence, requirement of semantic knowledge, corpus and training data, ability to identify semantic meaning, word order simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 55 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…Several methods to compare documents include word-based, keyword-based, n-gram-based, and Latent Semantic Analysis-based methodologies (see [16]). [17], on their review specifically about short text similarity (STS) tasks, broadens this classification to a more generic overview, to which he classifies the tasks as string-based, corpus-based, knowledge-based, and hybrid-based. Our work will use a hybrid approach (corpus-based and string-based), using the work of [14] as a reference method.…”
Section: Tweet Similarity Approach 41 Overviewmentioning
confidence: 99%
“…Several methods to compare documents include word-based, keyword-based, n-gram-based, and Latent Semantic Analysis-based methodologies (see [16]). [17], on their review specifically about short text similarity (STS) tasks, broadens this classification to a more generic overview, to which he classifies the tasks as string-based, corpus-based, knowledge-based, and hybrid-based. Our work will use a hybrid approach (corpus-based and string-based), using the work of [14] as a reference method.…”
Section: Tweet Similarity Approach 41 Overviewmentioning
confidence: 99%
“…A number of NLP methods, e.g. adapted from various text similarity measures, can then be employed to compare the reconstructed QUDs to the overt question to see whether and where they overlap (Croft et al, 2013;Prasetya et al, 2018;Prakoso et al, 2021). Evasive bullshitting by way of introducing novel QUDs (and pretending they answer the original one) occurs when the topic of question and answer matches, but the implicit QUDs differ strongly from the overt ones.…”
Section: Nlp-based Detection Of Persuasive Bullshitmentioning
confidence: 99%
“…So, NLP is based on textual similarity evaluation. [ 1 ] showed and discussed the popular methods used in evaluating short text similarity, such that they examined and compared each other and demonstrated how the approaches used in short text similarity evaluation changed over time. While some researchers, such as the work of [ 2 ], used several words overlapping methods to count the similar words between the learner’s answer and the model answer, this study concluded that the algorithm of the overlapping word cannot overcome the semantic similarity problems, such as some students can express the correct answer in words different than the model answer keywords.…”
Section: Introductionmentioning
confidence: 99%